RELASI EMOSIONAL NON-FISIK PEREMPUAN DALAM MASA IDDAH DI ERA MEDIA SOSIAL ANALISIS MAQASID AL-SYARI’AH DAN SADD AL-DZARI’AH - Yusita Tri Andani; Muhammad Zainuddin Sunarto (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study examines the phenomenon of non-physical infidelity through social media among women undergoing the iddah period, an issue that has developed along with the rapid development of digital technology. The purpose of this study is to analyze the forms of non-physical infidelity of women during the iddah period, the Islamic legal perspective on this phenomenon, and its impact on the objectives of iddah and the chances of reconciliation. This study is a normative-maqasid legal study with a textual approach, using secondary data analyzed through descriptive-analytical content analysis methods. The results show that women undergoing the iddah period are not permitted to interact digitally with non-mahram men without urgent reasons, because it can damage honor and reduce the chances of reconciliation. Non-physical infidelity, even though it does not involve physical contact, can damage the moral values ​​and sanctity of the iddah period. This study presents a methodological novelty by linking the phenomenon of non-physical emotional relationships on social media with the sadd al-dzari'ah approach as a preventive instrument in Islamic law.